2006
DOI: 10.1161/circulationaha.105.001370
|View full text |Cite
|
Sign up to set email alerts
|

Adenoviral Human BCL-2 Transgene Expression Attenuates Early Donor Cell Death After Cardiomyoblast Transplantation Into Ischemic Rat Hearts

Abstract: Background-Cell transplantation for myocardial repair is limited by early cell death. Gene therapy with human Bcl-2 (hBcl-2) has been shown to attenuate apoptosis in the experimental setting. Therefore, we studied the potential benefit of hBcl-2 transgene expression on the survival of cardiomyoblast grafts in ischemic rat hearts. Methods and Results-H9c2 rat cardiomyoblasts were genetically modified to express both firefly luciferase and green fluorescent protein (mH9c2). The cells were then transduced with ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
43
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(43 citation statements)
references
References 21 publications
0
43
0
Order By: Relevance
“…To further investigate mitochondrial mechanisms potentially involved, which may modulate apoptosis, we measured the antiapoptotic protein Bcl-2 (35), which constitutes a pivotal regulator of mitochondrial apoptosis (36). A recent study strengthens the emergent role for Bcl-2 in protecting cardiac cells against death, including apoptosis (37). Although others have found a reduction in the antiapoptotic protein Bcl-2 in chronic doxorubicin-induced cardiomyopathy (34), we found in the acute situation of our model no regulation of this protein at all.…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate mitochondrial mechanisms potentially involved, which may modulate apoptosis, we measured the antiapoptotic protein Bcl-2 (35), which constitutes a pivotal regulator of mitochondrial apoptosis (36). A recent study strengthens the emergent role for Bcl-2 in protecting cardiac cells against death, including apoptosis (37). Although others have found a reduction in the antiapoptotic protein Bcl-2 in chronic doxorubicin-induced cardiomyopathy (34), we found in the acute situation of our model no regulation of this protein at all.…”
Section: Discussionmentioning
confidence: 99%
“…Approaches to boosting cell survival for grafting applications in different tissues and organ systems have also been evaluated. Overexpression of Bcl-2 has been shown to improve survival of endothelial [81,82] and cardiac [83] cells implanted subcutaneously. Caspase inhibition provided to cultured cells, and delivered systemically after injection enhances survival of islet cells [84] and dopaminergic neurons [85,86].…”
Section: Strategies To Increase Cell Survivalmentioning
confidence: 99%
“…Growth factors continuously stimulate tyrosine kinase activity to suppress the proapoptotic and BH3-only family members, and thus prevent initiation of apoptosis (17,18). Enforced expression of the 26-kDa BCL2 antiapoptotic protein has been reported to result in enhanced survival and proliferation in several different systems (16,19,20). We demonstrated that mouse embryonic stem-cell (mESC) lines expressing the human BCL2 transgene could self-renew continuously under serum-free and feeder cell-free conditions (21), and improved efforts to identify and isolate mouse ES-derived HSC (22).…”
mentioning
confidence: 99%